Effects of Levonorgestrel Implants of One Rod and Two Rod on Lipid Profile, Follicle Stimulating Hormone (FSH), and Estradiol Levels in Acceptors : Efek Implan Levonorgestrel Satu Batang dan Dua Batang terhadap Profil Lipid, Kadar Follicle Stimulating Hormone (FSH), dan Estradiol pada Akseptor - Santa Maria; Heriyadi Manan; Theodorus Theodorus; Adnan Abadi (Indonesian Socety of Obstetrics and Gynecology, 2020)
Abstract Objective: To find out the comparison of the effect of one-rod and two-rod levonorgestrel implants on FSH, estradiol levels and increase in acceptor lipid profile after a 3-month evaluation in the Mother Hospital of Rika Amelia Palembang.Methods: This study was a phase III clinical trial,